"Hopeless, Sorry, Hopeless". Issue 3 (July 2015) - Hersh, Deborah
<x xml:space="preserve">Abstract</x> Despite widespread support for user involvement in health care, people with aphasia (PWA) report feeling ignored and disempowered in care contexts. They also rarely have the opportunity to give feedback on their experiences of care post-stroke. However, it is important for health care professionals to hear this feedback, both to understand the broader illness narrative and potentially to inform improved practice. Health care professionals who work with PWA should be trained and supported to co-construct narratives of feedback on care. In this article, I consider the knowledge, skills, and attitudes underpinning co-construction in this context and use examples from interviews with 2 PWA to illustrate narrative competence, the richness of their stories, and what lessons might be learned. The development of responsive, person-centered health care systems would be assisted by valuing such narratives and giving a voice to a group of people so familiar with health care services but also so rarely heard.